The effect of oxygen tension on human articular chondrocyte matrix synthesis: Integration of experimental and computational approaches. Issue 9 (5th May 2014) - Li, S.; Oreffo, R.O.C.; Sengers, B.G.; Tare, R.S.
ABSTRACT Significant oxygen gradients occur within tissue engineered cartilaginous constructs. Although oxygen tension is an important limiting parameter in the development of new cartilage matrix, its precise role in matrix formation by chondrocytes remains controversial, primarily due to discrepancies in the experimental setup applied in different studies. In this study, the specific effects of oxygen tension on the synthesis of cartilaginous matrix by human articular chondrocytes were studied using a combined experimental‐computational approach in a "scaffold‐free" 3D pellet culture model. Key parameters including cellular oxygen uptake rate were determined experimentally and used in conjunction with a mathematical model to estimate oxygen tension profiles in 21‐day cartilaginous pellets. A threshold oxygen tension (pO2 ≈ 8% atmospheric pressure) for human articular chondrocytes was estimated from these inferred oxygen profiles and histological analysis of pellet sections. Human articular chondrocytes that experienced oxygen tension below this threshold demonstrated enhanced proteoglycan deposition. Conversely, oxygen tension higher than the threshold favored collagen synthesis. This study has demonstrated a close relationship between oxygen tension and matrix synthesis by human articular chondrocytes in a "scaffold‐free" 3D pellet culture model, providing valuable insight into the understanding and optimization of cartilage bioengineering approaches. Biotechnol. Bioeng. 2014;111: 1876–1885. © 2014 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc.